AN EXPERIENCE WITH SIXTY CASES OF HAEMATOLOGICAL MALIGNANCIES; A CLINICO HAEMATOLOGICAL CORRELATION - Idris, Muhammad; Shah, S.H.; Fareed, Jamila; Gul, Nasreen (Journal of Ayub Medical College Abbottabad, 2004)
Background: Haematological malignancies are not uncommon in our area. Due to inadequate diagnostic facilities and lack of health education they are diagnosed at an advanced stage when treatment is either impossible or very difficult. In our study, sixty patients with haematological malignancies were studied from 1-1-1999 to 1-1-2001, at Ayub Teaching Hospital, Abbottabad. Methods: Patients were interviewed in detail, a thorough physical examination and blood tests including haemoglobin estimation, total and differential leukocyte count, platelets count, reticulocyte count and blood film examination was done on each patient. Bone marrow examination for routine giemsa staining and cytochemistry was also done in each case. Trephine biopsy was done in selected cases. Results: About 35.9% patients had acute myeloid leukemia, while 19.15% patients had acute lymphoblastic leukemia. Non Hodgkin’s lymphoma was seen in 15.39% cases. Among chronic leukemias, chronic lymphocytic leukemia outnumbered chronic myeloid leukemia (13.91% against 10.76%). Multiple myeloma was seen in 4.61% patients while a single patient had Hodgkin’s disease. Male to female ratio in haematological malignancies was 1.4:1 and majority of the patients (66.66) belonged to two districts (i.e. Mansehra and Abbottabad). Low grade fever, progressive pallor, weakness and body aches were the commonest symptoms (70% cases) while pallor was the frequently observed sign. Medium age for acute myeloid and acute lymphoblastic leukemia was 26 years and 7 years respectively. For chronic myeloid and chronic lymphocytic leukemia it was 22 years and 56 years respectively. In case of non Hodgkin’s lymphoma it was 22.5 years. Conclusion: In our study acute myeloid leukemia was the commonest type of haematological malignancy. Males were affected more than the females. Majority of the patients belonged to districts Mansehra and Abbottabad. Non specific symptoms like low grade fever, progressive pallor and bodyaches were the commonest symptoms while pallor was the most frequently observed sign. Key Words: Haematological malignancy, Clinicohaematological correlation, Leukemia